2012
DOI: 10.1002/jor.22215
|View full text |Cite
|
Sign up to set email alerts
|

α2β1 integrin and RhoA mediates electric field‐induced ligament fibroblast migration directionality

Abstract: Guided cell migration is important in tissue development, repair, and engineering. We have previously demonstrated that applied electric fields (EFs) enhanced and directed ligament fibroblast migration and collagen production, depending on EF parameters. Electrical stimulation is widely used for the treatment of pain and to promote wound healing. In orthopaedic practices, applied EFs promote bone healing and ligament repair in vivo. In the current study, stimulation waveforms used in physical therapy for promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…We previously reported that integrin mediates directional cell migration in applied EFs (17). The polarized distribution of integrin in response to EF was abolished with raft disruption, whereas raft polarization in EF was less influenced by functional blocking of integrin (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…We previously reported that integrin mediates directional cell migration in applied EFs (17). The polarized distribution of integrin in response to EF was abolished with raft disruption, whereas raft polarization in EF was less influenced by functional blocking of integrin (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Polarization of intracellular signaling molecules, including RhoA, src, and PI3K, mediates EF-induced directionality (7,17). To understand the role of raft in the polarization of these downstream factors, we examined their distribution in applied EF after raft disruption and found polarization of these signaling proteins was abolished (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations